Pengaruh Penggunaan Media Kongkrit Terhadap Hasil Belajar Matematika Siswa di Kelas III MI Yapip Pencong Kabupaten Gowa - Musdalifah Musdalifah; Andi Ardilla Wahyudi; Hamdana Hadaming (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The aim of this research is to determine the effect of using concrete media on the mathematics learning outcomes of class III students at MI Yapip Pencong, Gowa Regency. This type of research is Pre-Experimental Design research. The sample in this study was 10 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test.The research results showed that the student learning outcomes before being given treatment were 10 students with an average score of 53 and there were 4 students or 40% who were in the medium category, and 6 students or 60% who were in the low category. Meanwhile, after being given treatment, 10 students had an average score of 84 and there were 4 students or 40% who were in the very high category, 4 students or 40% who were in the high category, and 2 students or 20% who were in the medium category. The results of the t-test analysis of the influence of concrete media on student learning outcomes show that the significance value obtained is smaller than the alpha value set, namely 0.05 (0.010 < 0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted.Based on the results of the research that has been carried out, it is concluded that concrete media has an influence on mathematics learning outcomes for class III students at MI Yapip Pencong, Gowa Regency.